(untitled) (Global Journal of Science Frontier Research, 2016)
Sixty four wheat genotypes were tested in 8×8 simple lattice design at Ginchi, West Shewa in 2012/13 cropping season. The overall objective was to study the extent of genetic variability, heritability and genetic advance. Analysis of variance revealed that there was a significant difference among the sixty four genotypes for all the characters studied. The phenotypic coefficients of variation (PCV) values were higher than genotypic coefficients of variation (GCV) values for all the traits studied. Medium phenotypic coefficients of variation (PCV) and genotypic coefficients of variation (GCV) were recorded for plant height, number of kernels per spike, thousand kernels weight, grain yield per plot, biomass yield per plot and harvest index. Medium phenotypic coefficients of variation (PCV) and low genotypic coefficients of variation (GCV) values were displayed for days to heading.